UNIFIED HEALTH SYSTEM (SUS) IN ITS DICHOTOMY OF VARIABLES: THE CHALLENGES OF THE CITY OF TUPÃ AS AN EMERGENCY CARE REGION - dos Santos, Aloísio Cássio; Amaral, Amanda Frigulio; Loyola, Arthur Gomes; Oliveira, Eliza Cunha (Seven Editora, 2025)
This paper analyzes the creation and importance of the Unified Health System (SUS) in Brazil. Before its establishment, formalized by the 1988 Federal Constitution, the country’s health system was fragmented and unequal. The SUS was established with the goal of guaranteeing universal, free, and equal access to health care for the entire population. Its implementation represented a substantial advance, promoting the decentralization of services and a focus on primary care, prevention, and health promotion. This principle reflects the vision that "health is a right for all and a duty of the State," as emphasized by Paulo Capel Narvai (2022, p. 103). Despite notable achievements, such as expanded access to treatments and preventive programs, the system faces challenges that compromise its ability to fully serve the population. Problems such as underfunding, regional inequalities, and the social perception that health actions and services are not rights, but commodities (NARVAI, 2022) persist. However, it is concluded that the SUS continues to be one of the country’s greatest social achievements, essential to guarantee the well-being of millions of Brazilians. DOI: https://doi.org/10.56238/sevened2025.036-032